2022
DOI: 10.1186/s12943-022-01541-9
|View full text |Cite|
|
Sign up to set email alerts
|

A novel approach for relapsed/refractory FLT3mut+ acute myeloid leukaemia: synergistic effect of the combination of bispecific FLT3scFv/NKG2D-CAR T cells and gilteritinib

Abstract: Background Patients with relapsed/refractory acute myeloid leukaemia (AML) with FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) have limited treatment options and poor prognosis. Therefore, novel treatment modalities are needed. Since high expression of natural killer group 2 member D ligands (NKG2DLs) can be induced by FLT3 inhibitors, we constructed dual-target FLT3 single-chain fragment variable (scFv)/NKG2D-chimeric antigen receptor (CAR) T cells, and explored whether FLT3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 75 publications
(66 reference statements)
0
26
0
Order By: Relevance
“…One was two distinct scFvs 'hand-in-hand' on one cell, whereas the other was two independent CAR monomers with distinct scFvs on a single cell. Recent studies showed that bispecific CAR-T cells could enhance tumor-suppression capacity through dual antigen recognition and internal activation to effectively eradicate tumor cells 174 , 175 .…”
Section: Up-to-date Strategies For Car-t Cell Therapy To Address the ...mentioning
confidence: 99%
“…One was two distinct scFvs 'hand-in-hand' on one cell, whereas the other was two independent CAR monomers with distinct scFvs on a single cell. Recent studies showed that bispecific CAR-T cells could enhance tumor-suppression capacity through dual antigen recognition and internal activation to effectively eradicate tumor cells 174 , 175 .…”
Section: Up-to-date Strategies For Car-t Cell Therapy To Address the ...mentioning
confidence: 99%
“…Other clinical trials have targeted NKG2D, which is expressed on several subtypes of T cells, NK cells, and NKT cells [ 130 , 131 , 132 , 133 ]. Recent clinical trials of CAR-T therapy in AML and/or MDS are summarized in Table 3 .…”
Section: Car-tmentioning
confidence: 99%
“…The bispecific CAR T cells eliminated both primary FLT3mut and FLT3wt AML blasts, although the treatment effect on the FLT3mut AML blasts was more profound. The tumor-killing efficacy of CAR T cells improved dramatically when they were administered in combination with Gilteritinib both in vitro and in vivo [ 98 ].…”
Section: Flt3i: Indications Mechanisms Of Resistance In Vitro and In ...mentioning
confidence: 99%